Epistemologi: Satu Perbincangan Awal - Imam, Imam Abdul Fattah; Abdul Majid, Mohamad Kamil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
The epistemology is one of the major topics discussed in philosophy. This article proposes an introduction on some aspects of the epistemological problems including the sources of knowledge, its nature and the possibility of acquiring it.